Peningkatan Hasil Belajar Fisika MelaluiMetode Pembelajaran Survey, Question, Read, Recite, Dan Review (SQ3R) Pada Siswa Kelas XI-IPA 3 - Hasby Hasby (Universitas Negeri Makassar, 2021)
This study aims to describe the improvement in learning outcomes of students in class XI-IPA.3 SMA Negeri 1 Mallusetasi, Barru Regency through the Survey, Question, Read, Recite, and Review (SQ3R) Learning Method. This type of research is a classroom action research (PTK) which provides an overview of the application of the Survey, Question, Read, Recite, and Review (SQ3R) learning method. The subjects of this study were students of class XI-IPA.3 odd semester 2015/2016 academic year, amounting to 24 students consisting of 8 boys and 16 girls. The research results have shown good results, from student learning outcomes, with 79.17% classical completeness or as many as 19 students. Thus, it has fulfilled the classical success indicator, which is 75%. So that the conclusion in this study by applying the survey, question, read, recite, and review (SQ3R) learning method can improve the learning outcomes of Physics in class XI-IPA.3 Negeri 1 Mallusetasi, Barru Regency.